Prospective seroepidemiologic study on the role of Human Papillomavirus and other infections in cervical carcinogenesis: Evidence from the EPIC cohort - Castellsagué, X; Pawlita, M; Roura, E; Margall, N; Waterboer, T; Bosch, F; De Sanjosé, S; Gonzalez, C; Dillner, J; Gram, I; Tjønneland, A; Munk, C; et al. (Wiley-Liss Inc., 2014)
To evaluate prospectively the association between serological markers of selected infections, including HPV, and risk of developing cervical cancer (CC) and precancer, we performed a nested case-control study within the European Prospective Investigation into Cancer and Nutrition (EPIC) study that included 184 cases of invasive CC (ICC), 425 cases of cervical intraepithelial neoplasia (CIN) grade 3 or carcinoma in situ (CIS), and 1,218 matched control women. At enrollment participants completed lifestyle questionnaires and provided sera. Subjects were followed-up for a median of 9 years. Immunoassays were used to detect serum antibodies to Human Herpes Virus 2 (HHV-2), Chlamydia trachomatis (CT), Chlamydia pneumoniae, L1 proteins of mucosal and cutaneous HPV types, E6/E7 proteins of HPV16/18, as well as to four polyomaviruses. Adjusted odds ratios (OR) [and 95% confidence intervals (CI)] for CIN3/CIS and ICC risk were respectively: 1.6 (1.2-2.0) and 1.8 (1.1-2.7) for L1 seropositivity to any mucosal HPV type, 1.0 (0.4-2.4) and 7.4 (2.8-19.7) for E6 seropositivity to HPV16/18, 1.3 (0.9-1.9) and 2.3 (1.3-4.1) for CT seropositivity, and 1.4 (1.0-2.0) and 1.5 (0.9-2.6) for HHV-2 seropositivity. The highest OR for ICC was observed for HPV16 E6 seropositivity [OR-=-10.2 (3.3-31.1)]. Increasing number of sexually transmitted infections (STIs) was associated with increasing risk. Non-STIs were not associated with CC risk. In conclusion, this large prospective study confirms the important role of HPV and a possible contribution of CT and HHV-2 in cervical carcinogenesis. It further identifies HPV16 E6 seropositivity as the strongest marker to predict ICC well before disease development. What's New? Limited data are available from prospective studies concerning the role of past exposure to human papillomavirus (HPV) and other infections in cervical carcinogenesis. This study assessed associations between cervical cancer and pre-cancer and serological markers of exposure to mucosal and cutaneous HPVs, Chlamydia trachomatis (CT), Chlamydia pneumonia, human herpes virus-2 (HHV-2), and polyomaviruses using a nested case-control design within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Associations were found for mucosal HPVs, CT, and HHV-2. A greater number of sexually transmitted diseases further raised the risk of cervical cancer. © 2013 UICC.